MESIKHAT DALAM KAJIAN ESTETIKA SIMBOLIS PADA RUMAH ADAT ALAS ACEH TENGGARA - Kafri, Saniman Andi (Jurnal Ilmu Budaya, 2018)
Mesikhat ornament is one of heritage artworks made by people in Alas tribe. As one of the cultural heritages, the motif of Mesikhat ornament which is really important as th eaesthetic symbol for Alas tribe in Southeast Aceh. People in south Aceh call all of carve motif that come from south Aceh as Meshikat. However Meshikat is originally came from Alas tribe. Meshikat motif can be found in traditional house, traditional costume, bag, wallet and others accessories. Meshikhat ornament had existed before the Independence day of Indonesia. However, it became popular around 1990 when these wing machine was firstly used in south east of Aceh. Formerly, meshikat is only applied in traditional house but nowadays the motif is also used in fashion, bag, wall and others accessories. Meshikat, that is applied in traditional house and costume, has five colors; red, yellow, green, white and black. The basic colors symbolize different meanings. For example red symbolizes the bravery, green symbolizes the fertility, yellow shows the glory or the greatness, white symbolizes the purity, and black symbolizes the leadership. The idea of Meshikat motif originated from plants, animals, social life and chess board. The descriptions are applied in the form of two dimension motif without ignoring the aesthetic aspect and the meaning of these objects. Meshikat, notif present many interpretations and messages such as social message, moral value, and spiritual message depending on the motifs.